Livelihood Diversification Based On Strengthening Social Cohesion To Empower Landless Peasants - Dumasari, Dumasari; Dharmawan, Budi; Santosa, Imam; Darmawan, Wayan; Aisyah, Dinda Dewi (The journal of contemporary issues in business and government, 2021)
Landless peasants experience problems such as difficulty earning livelihoods, low income, economic marginalization, and poverty. Therefore, this study explored diversification of livelihoods and strengthening social cohesion among landless peasants. It focused on the villages of Baturaden and Purbalingga Wetan, Central Java Province, Indonesia, using an intrinsic case study method. The results revealed that landless peasants were experiencing social differentiation, which weakened social cohesion and made cooperation, social networks, solidarity, and collectivity tenuous. Landless peasants classified into: tenants, tenant cultivators, sharecroppers, and farm laborers. Sharecoppers and farm laborers suffered the most from weakening social cohesion and had minimal access to economic opportunities on or off farms. Farm laborers were marginalized by low wages and difficulty finding employment. Overall, the study found the need for landless peasants to diversify their livelihoods, and suggest that strengthening social cohesion is important for sharecroppers and farm laborers to achieve guaranteed livelihoods and economic security.